Adaptation through chromosomal inversions in Anopheles - Ayala, Diego; Ullastres, Anna; González, Josefa (Frontiers in Genetics, 2014)
Chromosomal inversions have been repeatedly involved in local adaptation in a large number of animals and plants. The ecological and behavioral plasticity of Anopheles species - human malaria vectors - is mirrored by high amounts of polymorphic inversions. The adaptive significance of chromosomal inversions has been consistently attested by strong and significant correlations between their frequencies and a number of phenotypic traits. Here, we provide an extensive literature review of the different adaptive traits associated with chromosomal inversions in the genus Anopheles. Traits having important consequences for the success of present and future vector control measures, such as insecticide resistance and behavioral changes, are discussed.